PELATIHAN PENERAPAN MODEL REALISTIC MATHEMATICS EDUCATION BERBASIS ETNOMATEMATIKA TABUT TERHADAP KEMAMPUAN LITERASI MATEMATIKA SISWA KELAS IV SDN 67 KOTA BENGKULU - Neza Agusdianita; Victoria Karjiyati; Sri Ken Kustianti (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of this Community Service Activity is to increase teacher knowledge about the Application of the Realistic Mathematics Education (RME) Based Ethnomatic Tabut and  develop students' mathematical literacy in Elementary Schools. Through this activity it is expected to improve the skills of teachers in designing and evaluating meaningful and fun mathematics learning. The method used in this Community Service Activity is training. The instruments used in this PPM activity were observation sheets, interview sheets, and training modules. This activity data analysis is descriptive qualitative. The result of this research is that training activities for the application of the Realistic Mathematics Education Model Based on Ark Ethnomatics have been carried out which can develop students' Mathematical Literacy Ability. Through this activity the community service team donated 5 units of miniature ark and training modules to partner schools.